Higuchi Fractal Dimension Analysis of EEG Signal Before and After OM Chanting to Observe Overall Effect on Brain - Bhavna P Harne (International Journal of Electrical and Computer Engineering (IJECE), 2014)
The OM chanting is one type of the meditation. In the present paper, the author tried to observe its effect on the brain. To obtain insight of the brain, the author recorded EEG signal before and after OM chanting for 10 subjects. Author used a technique of the complexity measure based on fractal analysis to compare the EEG signal before and after OM chanting. Time domain fractal dimension was calculated using Higuchi algorithm. (HFD).Paper present the results based on average HFD all over the electrodes for each subject before and after OM chanting.DOI:http://dx.doi.org/10.11591/ijece.v4i4.5800